Culture as Element of EU Regional Policy at the Turn of XXI Century: Example of Spain and Portugal - T. P. Nesterova; E. O. Zudova (Научный диалог)
The experience of cultural policy implementation in the context of modern regional policy of the European Union (EU) is considered. Special attention is paid to the implementation of this direction in the countries of the Iberian Peninsula: Spain and Portugal. The relevance of the study stems from the importance of cultural cooperation at this stage of the development of Europe, which now includes not only the direct cooperation of specialists and increasing access to cultural and historical heritage, but also innovation sphere, one of the priorities of the EU in this area. The experience of implementation of regional programs of EU cooperation in the field of culture in the countries of the Iberian Peninsula is examined, the progress and efficiency of the implementation of cultural projects in Spain and Portugal are revealed. In particular, the authors focus on programs “Ariane,” “Kaleidoscope,” “Raphael,” “Culture 2000”, “Culture 2007-2013”, “European cultural capital” and other projects of special interest for the study of cultural policy of the EU in Southern Europe. A review of official materials of the EU is made: agreements, strategic framework, etc., as well as the works of European and Russian researchers. It is concluded that at present time the culture is an integral part of EU regional policy and represents a powerful tool for socio-economic development of territories, in particular, regions of Spain and Portugal.